Lessons learned from comparing self-collected vs. physician-collected vaginal swabs for diagnosing infections in resource-limited settings: a 24-year review - Lachyan, Dr.Abhishek; Khunger, Dr.Niti; Bharti, Dr.Rekha; Sharma, Dr.Roshni; Mehrotra, Dr.Krati; Goyal, Dr.Abhay (Brazilian Journal of Sexually Transmitted Diseases, 2024)
Introduction: Reproductive health is essential for women’s overall well-being, yet vaginal infections like Bacterial Vaginosis (BV), Candidiasis, and Trichomoniasis are prevalent and can lead to severe complications if left untreated. In high-income countries, healthcare systems are generally equipped to handle these infections; however, in resource-limited settings, barriers such as geographic isolation, financial constraints, and social stigmas hinder access to effective care. Self-collected vaginal swabs present a promising alternative to traditional physician-collected samples, offering potential benefits in these underserved regions. Objective: This study aims to evaluate the feasibility, diagnostic accuracy, and community acceptance of self-collected vaginal swabs compared to physician-collected samples for diagnosing bacterial vaginosis, candidiasis, and trichomoniasis in resource-limited settings, and to explore strategies for the broader implementation of this approach to improve women’s reproductive health. Methods: This narrative review synthesizes literature on the effectiveness, feasibility, and community acceptance of self-collected vaginal swabs compared to physician-collected samples for diagnosing BV, Candidiasis, and Trichomoniasis. A systematic search was conducted across PubMed, Google Scholar, and institutional repositories for studies from January 2000 to May 2024. The review encompasses various sections, including background on the significance of timely diagnosis, initiatives empowering women through self-collection, challenges and successes of these initiatives, and strategies for quality assurance and policy advocacy. Results: Selfcollected vaginal swabs were found to be as accurate as physician-collected samples in diagnosing BV, Candidiasis, and Trichomoniasis. The method enhances accessibility and reduces stigma, showing potential for broader application in community health settings. Conclusion: Self-collected vaginal swabs represent a viable solution to reproductive health challenges in resource-limited settings. They offer comparable diagnostic accuracy, enhance accessibility, and can reduce cultural barriers to seeking care. Future efforts should focus on community education, technological innovations, and policy reforms to maximize the effectiveness and sustainability of this approach in improving global women’s health.